Psychiatric Nurse-Led Interventions: A Pathway to Improved Coherence and Social Support in Alcohol Dependency - Kala Paramasivam; Theranirajan Ethiraj; Shankar Shanmugam Rajendran; Venkatesh Mathankumar; Anbalagan Marudan; Balasubramanian Sri Vidhya; Schwartzlin V. Sathiyanathan (Journal of Pharmacy and Bioallied Sciences)
Background: Alcohol dependency is a significant global health issue, marked by continuous use despite harmful effects. Psychiatric nurse-led interventions are crucial for addressing the complex needs of alcohol-dependent individuals by enhancing coherence and social support. Methods: A quasiexperimental study at the De Addiction Department in Chennai involved 120 male clients aged 20–45 years, divided into experimental and control groups. Results: The experimental group showed significant improvements in coherence and social support postintervention. Conclusion: This study underscores the effectiveness of psychiatric nurse-led interventions in promoting resilience and social support in alcohol-dependent clients, essential for effective addiction treatment.